Growth, exploitation and class inequalities - Giorgos Galanis; Roberto Veneziani; Naoki Yoshihara (Queen Mary University of London, School of Economics and Finance, 2017)
This paper provides a formal dynamic analysis of exploitation, class inequalities and profits. A stylised model of a capitalist economy with two classes - workers and capitalists - is considered which extends Roemer [21, 22]. First, a dynamic generalisation of a key Marxian insight is provided by proving that the profitability of capitalist production is synonimous with the existence of exploitation. Second, it is shown that, in a competitive environment, asset inequalities are fundamental for the emergence of exploitation, but they are not sufficient for its persistence, both in equilibria with accumulation and growth, and, perhaps more surprisingly, in stationary intertemporal equilibrium paths. Finally, it is shown that labour-saving technical progress may yield persistent exploitation by ensuring the persistent abundance of labour.
Keywords: E11; D51; D63; C61; B24; 330; Dynamics; Accumulation; Exploitation; Classes